Culture and Modern Indonesian Women: Navigating Tradition and Change - Isro'iyah, Latifatul; Riinawati (Penerbit Lafadz Jaya, 2025)
This article explores the intricate relationship between culture and the contemporary status of women in Indonesia, reflecting on how traditional values interact with modern societal changes. In recent decades, Indonesia has witnessed significant transformations, influenced by globalization, technological advancements, and women's empowerment movements. The paper examines the way modern Indonesian women negotiate their identities within a cultural framework that historically espouses patriarchal norms. Through qualitative analysis, this research reveals the duality faced by women balancing cultural expectations with personal aspirations. It highlights the roles of education, employment, and social media in reshaping women's perspectives and contributing to the evolving discourse on gender equality. Conclusively, this study emphasizes that while modern Indonesian women are increasingly pushing against the constraints of traditional culture, they continue to navigate a complex landscape where these cultural narratives shape their realities. The findings suggest that fostering an understanding of cultural contexts is necessary for promoting gender equality in Indonesia.